PEMBERIAN RESTITUSI TERHADAP KORBAN TINDAK PIDANA KEKERASAN SEKSUAL (STUDI PUTUSAN NOMOR XX/PID.B/2023/PN FFK): Providing Restitution To Victim Crime Of Sexual Violence (Study Decision Number Xx/Pid.B/2023/Pn Ffk) - Nauli Amari Putra; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2025)
In Decision Number XX/Pid.B/2023/PN.Ffk concerning a criminal act of sexual violence, the victim must receive adequate protection to support their physical and psychological recovery. Furthermore, if the perpetrator is sentenced to more than four years in prison, the victim has the right to claim restitution. This study examines the responsibility of law enforcement, particularly judges, in determining restitution for victims of sexual violence based on Decision Number XX/Pid.B/2023/PN.Ffk. In this ruling, the judge categorized the crime as sexual exploitation, which is considered inaccurate. The defendant was found guilty of committing a criminal offense by using violence or threats to coerce a woman—who also served as a victim witness—into engaging in sexual relations outside of marriage. This research employs a normative approach with an analytical-descriptive method, drawing conclusions through deductive reasoning. The findings highlight that, under Article 30 of Law Number 12 of 2022 on Criminal Acts of Sexual Violence, law enforcement officials are obligated to inform victims of their right to restitution. Given that the perpetrator received a sentence exceeding four years, this case necessitates restitution as a fundamental aspect of justice for the victim.